Caregiver Burden in Late-Stage Parkinsonism and Its Associations. (January 2022) - Kalampokini, Stefania; Hommel, Adrianus L. A. J.; Lorenzl, Stefan; Ferreira, Joaquim J.; Meissner, Wassilios G.; Odin, Per; Bloem, Bastiaan R.; Dodel, Richard; Schrag, Anette-Eleonore
Background: Patients in the late stages of parkinsonism are highly dependent on others in their self-care and activities of daily living. However, few studies have assessed the physical, psychological and social consequences of caring for a person with late-stage parkinsonism. Patients and methods: Five hundred and six patients and their caregivers from the Care of Late Stage Parkinsonism (CLaSP) study were included. Patients' motor and non-motor symptoms were assessed using the UPDRS and Non-motor symptom scale (NMSS), Neuropsychiatric inventory (NPI-12), and caregivers' health status using the EQ-5D-3 L. Caregiver burden was assessed by the Zarit Burden Interview (ZBI). Results: The majority of caregivers were the spouse or life partner (71.2%), and were living with the patient at home (67%). Approximately half of caregivers reported anxiety/depression and pain/discomfort (45% and 59% respectively). The factors most strongly associated with caregiver burden were patients' neuropsychiatric features on the total NPI score (r = 0.38, p < 0.0001), total NMSS score (r = 0.28, p < 0.0001), caring for male patients and patients living at home. Being the spouse, the hours per day assisting and supervising the patient as well as caregivers' EQ-5D mood and pain scores were also associated with higher ZBI scores (all p < 0.001). Conclusion: The care of patients with late stage parkinsonism is associated with significant caregiver burden, particularly when patients manifest many neuropsychiatric and non-motor features and when caring for a male patient at home.